Determining the rational composition of tribologically active additive to oil to improve characteristics of tribosystems - Aulin, Viktor; Hrynkiv, Andrii; Lysenko, Sergii; Zamota, Taras; Pankov, Andrii; Tykhyi, Andrii (Eastern-European Journal of Enterprise Technologies, 2019)
The conducted studies of the formation of the rational composition of a tribologically active additive to basic oil showed the possibility to improve the characteristics of tribosystems. It was revealed that this tribologically active additive enables the formation of tribological properties that ensure normal working conditions for the operation of the mated parts of a tribosystem. Based on the optimization of technical condition of a tribologically active additive, the rational values of each of its components were obtained. Optimization was carried out on condition that the magnitude of wear should be minimized, while critical load and welding load should be maximized. Based on the experimental database, on a four-ball friction machine, the equations for each of the response functions of the resulting features were obtained. The obtained regression equations and values of desirability function of the order of 0.698 allow determining the composition of a tribologically active additive: metakaolin, dispersive clay powder from Katerynivka deposit, sodium oleate, hydroxide of lithium and sulfur. It was established that when using the obtained tribologically active additive under laboratory conditions, the decrease in the wear of samples by 26.8 %, the increase in critical load by 17.2 %, the increase in welding load by 4.89 % were observed. Analysis of the experimental data shows that it is possible to use the proposed tribologically active additive in contact loading at the contact up to 1078 N and at peak overload up to 2,372 N. Research results give grounds to argue that the proposed tribologically active additive makes it possible to improve the characteristics of tribosystems. It can be useful for service and motor transport companies during technical servicing and in production of composite oil